85.0k views
4 votes
Perform the following transformations in the pictures below.

Perform the following transformations in the pictures below.-example-1
Perform the following transformations in the pictures below.-example-1
Perform the following transformations in the pictures below.-example-2
User Hstay
by
5.2k points

2 Answers

5 votes

I’m not sure, sorry!

User Stativ
by
5.8k points
4 votes

QUESTION A

ΔALT has coordinates
A(-5,-1),L(-3,-2),T(-3,2).

If we translate by the rule
(x,y)\rightarrow (x+6,y-3)

Then;


A(-5,-1)\rightarrow (-5+6,-1-3)=(1,-4).


B(-3,-2)\rightarrow (-3+6,-2-3)=(3,-5).


T(-3,2)\rightarrow (-3+6,2-3)=(3,-1).

A reflection over the y-axis has the mapping


(x,y)\rightarrow (-x,y)

If we reflect the resulting points over the y-axis, we obtain,


A(-5,-1)\rightarrow (1,-4)\rightarrow A'(-1,-4).


B(-3,-2)\rightarrow (3,-5)\rightarrow B'(-3,-5).


T(-3,2)\rightarrow (3,-1)\rightarrow C'(-3,-1).

QUESTION B

ΔTAB has vertices
T(2,3),A(1,1),B(4,-3).

A reflection over the x-axis has the mapping


(x,y)\rightarrow (x,-y)

A reflection over the y-axis also has the mapping;


(x,y)\rightarrow (-x,y)

If we reflect ΔTAB over the x-axis and reflect the resulting image over the y-axis, we obtain;


T(2,3)\rightarrow (2,-3) \rightarrow T'(-2,-3)


A(1,1)\rightarrow (1,-1) \rightarrow A'(-1,-1)


B(4,-3)\rightarrow (4,3) \rightarrow B'(-4,3)

QUESTION C

ΔALT has vertices
A(-5,-1),L(-3,-2),T(-3,2).

A
90\degree clockwise rotation about the origin has the mapping;


(x,y)\rightarrow (y,-x)

A reflection in the line y=x also has the mapping;


(x,y)\rightarrow (y,x)

When we rotate the given triangle
90\degree clockwise about the origin, and then reflect the image over the line y=x, we obtain;


A(-5,-1)\rightarrow (-1,5)\rightarrow A'(5,-1)


L(-3,-2)\rightarrow (-2,3)\rightarrow L'(3,-2)


T(-3,2)\rightarrow (2,3)\rightarrow T'(3,2)

QUESTION D

ΔTAB has vertices
T(2,3),A(1,1),B(4,-3).

A reflection over the y-axis has the mapping;


(x,y)\rightarrow (-x,y)

The rule for the given translation is


(x,y)\rightarrow (x+2,y-1)

If reflect the given triangle over the y-axis and translate using the rule
(x,y)\rightarrow (x+2,y-1), we obtain;


T(2,3)\rightarrow (-2,3)\rightarrow (-2+2,3-1)=T'(0,2)


A(1,1)\rightarrow (-1,1)\rightarrow (-1+2,1-1)=A'(1,0)


B(4,-3)\rightarrow (-4,-3)\rightarrow (-4+2,-3-1)=B'(-2,-4)

User Notedible
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.